A conserved signalling network regulates Epichloë festucae cell-cell fusion and the mutualistic symbiotic interaction between E. festucae and Lolium perenne : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy (PhD) in Genetics at Massey University, Manawatu, New Zealand - Green, Kimberly Anne (Massey University, 2016)
Epichloё festucae is a filamentous fungus that forms a mutually beneficial symbiotic association with Lolium perenne. The NADPH oxidase complex components noxA, noxR and racA, the transcription factor proA, and the cell wall integrity (CWI) MAP kinases, mkkA and mpkA, are required for mutualistic E. festucae-L. perenne associations and cell-cell fusion. Homologues of these genes in Neurospora crassa, Sordaria macrospora and Podospora anserina are required for cell-cell fusion and sexual fruiting body maturation, thereby establishing a link between self signalling and hyphal network formation in the E. festucae-L. perenne symbiosis. In Podospora anserina, IDC2 and IDC3 are required for cell-cell fusion, crippled growth and fruiting body formation. In S. macrospora and N. crassa, components of the STRIPAK complex regulate cell-cell fusion and fruiting body formation. The aim of this project was to test if E. festucae homologues of IDC2 and IDC3, and the STRIPAK complex protein MOB3, named SymB, SymC and MobC, respectively, are also required for cell-cell fusion and plant symbiosis. Gel shift assays showed the promoters of symB and symC are targets for the transcription factor ProA. In culture, the frequency of cell-cell fusion of ΔmobC was reduced, but in ΔsymB and ΔsymC mutants, totally abolished. All three mutants hyperconidiated and formed intra-hyphal hyphae. Plants infected with these mutants were severely stunted and hyphae exhibited proliferative growth and increased colonisation of the intercellular spaces and vascular bundles. Expressoria formation, structures allowing colonisation of the leaf surface, was reduced in ΔmobC, and abolished in ΔsymB and ΔsymC mutants. Microscopy analyses showed SymB-GFP and SymC-mRFP1 co-localise to the plasma membrane and septa. SymC also localised to highly dynamic punctate structures. Although ΔsymB and ΔsymC phenotypes are identical to ΔmpkA, and the E. festucae pheromone response pathway scaffold ΔidcA mutants, MpkA and MpkB phosphorylation and cellular localisation was unchanged compared to wild-type. Using yeast-two-hybrid assays, an interaction between SymC and the STRIPAK complex associated protein GPI1 was demonstrated. Collectively these results show that MobC, SymB and SymC are required for E. festucae cell-cell fusion and host symbiosis. It is proposed that SymB and SymC interact to form a sensor complex at the cell wall which regulates cell-cell fusion in culture and hyphal network development in planta.
Content redacted from thesis for copyright reasons: Figure 1.1 Page 4 Schardl, C. L. (2001) Epichloë festucae and related mutualistic symbionts of grasses. Fungal Genet. Biol., 33, 69-82. http://www.sciencedirect.com/science/article/pii/S1087184501912757 Schardl, C. L., Young, C. A., Hesse, U., Amyotte, S. G., Andreeva, K., Calie, P. J., et al . (2013) Plant-symbiotic fungi as chemical engineers: Multigenome analysis of the Clavicipitaceae reveals dynamics of alkaloid loci. Plos Genetics, 9(2), e1003323. http://journals.plos.org/plosgenetics/article?id=10.1371/journal.pgen.1003323 Christensen, M. J., Bennett, R. J., Ansari, H. A., Koga, H., Johnson, R. D., Bryan, G. T., et al. (2008) Epichloë endophytes grow by intercalary hyphal extension in elongating grass leaves. Fungal Genet. Biol., 45, 84-93. http://www.sciencedirect.com/science/article/pii/S1087184507001259 Becker, M., Becker, Y., Green, K. & Scott, B. (2016) The endophytic symbiont Epichloë festucae establishes an epiphyllous net on the surface of Lolium perenne leaves by development of an expressorium, an appressorium-like leaf exit structure. New Phytol., 211, 240-254. http://onlinelibrary.wiley.com/doi/10.1111/nph.13931/abstract Figure 1.2 Page 6 Scott, B. (2015) Conservation of fungal and animal nicotinamide adenine dinucleotide phosphate oxidase complexes. Mol Microbiol. 95(6):910-3. doi: 10.1111/mmi.12946. http://onlinelibrary.wiley.com/doi/10.1111/mmi.12946/abstract;jsessionid=087348D78C98893FF6F685B4A3D31179.f01 t03. Figure 1.3 Page 9 Haruo Saito & Kazuo Tatebayashi (2004) Regulation of the Osmoregulatory HOG MAPK Cascade in Yeast. The Journal of Biochemistry. 136 (3): 267-272. http://jb.oxfordjournals.org/content/136/3/267.abstract Figure 1.4 Page 10 Eaton, C., Mitic, M., Scott., B (2012) Signalling in the Epichloë festucae: Perennial Ryegrass Mutualistic Symbiotic Interaction. Signaling and Communication in Plant Symbiosis, pp.143-181. DOI: 10.1007/978-3-642-20966-6_7. http://link.springer.com/chapter/10.1007%2F978-3-642-20966-6_7 Figure 1.5 Page 14 Kück, U., Pöggeler, S., Nowrousian, M., Nolting, N., Engh, I., (2009) Sordaria macrospora, a model system for fungal development. In: Anke, T., Weber, D. (Eds.), The Mycota XV, Physiology and Genetics. Springer, Berlin/Heidelberg, pp. 17–39. http://homepage.rub.de/minou.nowrousian/Reprints/2009Mycota.pdf Figure 1.6 Page 16 Coppin, E., Debuchy, R., S. Arnaise, & Picard, M. (1997) Mating types and sexual development in filamentous ascomycetes. Microbiology and Molecular Biology Reviews, 61, 411-428. http://mmbr.asm.org/content/61/4/411.abstract Aldabbous, M. S., Roca, M. G., Stout, A., Huang, I. C., Read, N. D. & Free, S. J. (2010) The ham-5, rcm-1 and rco-1 genes regulate hyphal fusion in Neurospora crassa. Microbiology, 156, 2621- 2629. https://www.ncbi.nlm.nih.gov/pmc/articles/PMC3068686/pdf/2621.pdf Silar, P., Lalucque, H., & Vierny, C. (2001) Cell degeneration in the model system Podospora anserina. Biogerontology, 2, 1–17. https://www.ncbi.nlm.nih.gov/pubmed/11708613 Jamet-Vierny, C., Debuchy, R., Prigent, M. & Silar, P. (2007) IDC1, a pezizomycotina-specific gene that belongs to the PaMpk1 MAP kinase transduction cascade of the filamentous fungus Podospora anserina. Fungal Genet. Biol., 44, 1219-1230. http://fulltext.study/preview/pdf/2181591.pdf Figure 1.7 page 20 Fleißner, A., Leeder, A. C., Roca, M. G., Read, N. D. & Glass, N. L. (2009) Oscillatory recruitment of signaling proteins to cell tips promotes coordinated behavior during cell fusion. Proc. Natl. Acad. Sci. USA, 106, 19387-19392. http://www.pnas.org/content/106/46/19387.long Figure 1.8 page 22 Kück, U., Beier, A. M. & Teichert, I. (2016) The composition and function of the striatin-interacting phosphatases and kinases (STRIPAK) complex in fungi. Fungal Genet. Biol., 90, 31-38. http://www.sciencedirect.com/science/article/pii/S1087184515300347 Figure 4.8 page 143 Frey, S., Lahmann, Y., Hartmann, T., Seiler, S. & Pöggeler, S. (2015) Deletion of Smgpi1 encoding a GPI-anchored protein suppresses sterility of the STRIPAK mutant ΔSmmob3 in the filamentous ascomycete Sordaria macrospora. Mol. Microbiol., 97, 676-697. http://onlinelibrary.wiley.com/doi/10.1111/mmi.13054/suppinfo
Keywords: Epichloe; Lolium perenne; Genetics; Cell hybridization; Plant cellular signal transduction; Plant molecular biology; Research Subject Categories::NATURAL SCIENCES::Biology::Cell and molecular biology